Development of Planting Media for Agricultural Land Prone to Waterlogging - Sugiarto, Ari; Syafriyandi, Debby; Yovanda, Ridho (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
Waterlogging is a serious problem currently being faced in the agricultural sector. Climate change has increased the frequency of extreme rainfall events, which has increased the potential for agricultural land flooding. Therefore, innovations in planting media that can float during waterlogging are required. The purpose of this study was to create a planting medium based on simple automatic water flow and excess water control using a climate-based approach and plant water needs. The study stages were divided into three categories: climate data, planting media design and simulation, and field tests. The results of this study show that the design of planting media that considers plant water needs based on the amount of water lost can save water. The application of a drainage system on the side of the planting media prevented plant death in the planting media due to waterlogging, based on projections of an increase in extreme R-events. The use of plastic bottles in the design of the planting media was effective in providing buoyancy to the planting media during waterlogging. The developed planting medium is suitable for adaptation to agricultural land that is prone to waterlogging amidst the threat of the climate crisis that the world is currently facing.